The 2014 European Elections in Romania - Burean, Toma; Lupu, Horia; Badescu, Gabriel (Political Preferences, 2014)
The 2014 European elections in Romania represented a test for the political parties preparing for the presidential elections at the end of the same year. Firstly, we analyze the political context in which the European elections took place. Since 2012 the changing governing coalitions have created an unstable party system with many politicians shifting party allegiances. Several high ran- king party officials were considered suspicious for corruption acts and this affected the nomination of candidates. Secondly, we show that although the ideological allegiance of citizens and political parties increased since 2012, the match between policy preferences of political party and their supporters continues to be remarkably low. Finally we discuss several effects of the European elections, including difficulties in appointing candidates and creating electoral coalitions for the presidential elections encountered by the center right wing parties. Key words: EP election 2014, party system, Romania, political competition, European Parliament